HUBUNGAN MORFOMETRI DENGAN PRODUKSI SUSU SAPI PERAH PERANAKAN FRIESIAN HOLSTEIN (PFH) - Putra, Yudhistira Eka; Mulyati, Sri; Mumpuni S., Sri (Ovozoa: Journal of Animal Reproduction, 2019)
Dairy cow's is one of an animal which produce milk. It capable to supply the high necessary of milk in Indonesia. Many factors can influence milk production. Genetic, age, udder size, weight, lactation period, feed are the important part to decided milk production. The research aimed to study the correlation of morphometry based on chest circumference, body length, height, udder circumference, high of udder toward milk production. Data taken in form of chest circumference, body length, height, udder circumference, high of udder, and milk production. Data have been collated and analysize using regression analysis with SPSS software. The result showed that high of udder have a correlation with milk production. Chest circumference, body length, height, and udder circumference have no showed a correlation with milk production.